"I am not delusional!" Sensory dysaesthesia secondary to degenerative cervical myelopathy. Issue 4 (11th April 2019) - Mowforth, Oliver Daniel; Davies, Benjamin Marshall; Kotter, Mark Reinhard
Abstract : Degenerative cervical myelopathy (DCM) is the most common cause of adult spinal cord dysfunction, most classically presenting with a broad-based gait and clumsy hands. Limb sensory loss and paraesthesia are considered common symptoms of DCM. However, we report an unusual case of a patient presenting with prominent and atypical sensory symptoms. The patient repeatedly presented to accident and emergency complaining of her body resembling a wet gel-like substance that she attributed to the use of olive oil moisturising cream. The patient was found to have myelopathic signs on examination and MRI consistent with severe cervical myelopathy. She subsequently underwent successful decompressive anterior cervical discectomy, as recommended by international guidelines. This case serves to remind health professionals of uncommon presentations of common disease and the importance of maintaining a wide initial differential diagnosis.